Współdziałanie logistyczne małych i średnich przedsiębiorstw w organizacji sieciowej - Mucha, Beata (Cooperation in the Logistic Area of SME in the Network Organization, 2005)
The aim of this paper is to discuss the idea of cooperation between small and medium sized companies and to determine the areas of cooperation between the small and medium sized companies within a network organization. The paper also describes a case of such cooperation based on the example of a German logistic company FKG, that by having offered complex logistic services has not only survived but developed and strengthened its competitive position.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 337-343